Pengaruh Kecerdasan Emosional Terhadap Kinerja Pegawai Di Kantor Kecamatan Sape Kabupaten Bima - Wulandari, Wulandari; Burhanuddin, Burhanuddin; Mustari, Nuryanti (Universitas Muhammadiyah Makassar, 2021)
This study purposed to determine the response of respondents about emotional intelligence, employee performance, the influence of emotional intelligence on employee performance at the Sape District Office in Bima Regency. This type of research used quantitative study with a type of survey , data collection used a sample of 54 people and 34 people who frequently interact with district officials. The sampling technique in this study used a saturated sample, so that a sample of 88 was obtained. The results of this study showed that the emotional intelligence of employees at the Sape District Office in Bima was categorized very high, as evidenced by an average value of 4.53, the performance of employees at the Sape District Office Bima Regency was categorized very high, this was evidenced by an average value of 4.56, emotional intelligence had a positive and significant effect on employee performance at the Sape District Office in Bima. This was evidenced by the value of 5.345 ≥ 1.662 and the significance value of 0.000 ≤ 0.050. The performance of the employees at the Sape District Office in Bima Regency was 24.9%. While the remaining 75.1% was influenced by other variables which was not researched in this study.